Direct conversion of injury-site myeloid cells to fibroblast-like cells of granulation tissue - Mithun Sinha (Nature Portfolio, 2018)
At the site of injury, macrophages exit their characteristic phenotype undergoing direct conversion to fibroblasts. Keratinocyte-derived miR-21, packaged in extracellular vesicles, enables such plasticity which accounts for the vast majority of all fibroblasts in the granulation tissue.